Hubungan Frekuensi dan Waktu Kawin dengan Jumlah Anak Sekelahiran pada Anjing Golden Retriever yang Dipelihara Di Kota Denpasar - Oktaviami, Tessa Yuli; Indira Laksmi, Desak Nyoman Dewi; Puja, I Ketut (Veterinary Science and Medicine Journal; Vol. 1 No. 1 2013, 2013)
This retrospective study was conducted to know the relation between time and frequency of mating on litter size of Golden Retriver  in Denpasar Region. Mating incident records of 19 Golden Retrievers from 8 kennels were compiled to be analyzed. These data can be use as a reference in effort to maximize the amount of  Golden Retriever clans. The result showed that the three times of mating on the 10 th , 12 th and 14 th day after onset of proestrus produced the most litter size 10 ± 2.82. However, mating twice on wice on 9 th and 11 th after onset of proestrus produced a litter size of 8.50 ± 0.70. The statistic analysis depicted that there was no significant relationship between mating frequencies and mating time on litter size.
Keywords: Golden Retriever; mating frequency; mating time; litter size